Particle electric dipole moments - Pendlebury,JM; Hinds,EA (Nuclear Instruments and Methods in Physics Research Section A Accelerators Spectrometers Detectors and Associated Equipment, 2000)
Measurements of particle electric dipole moments (EDMs) continue to put power constraints on theories of T-symmetry and CP-symmetry violation, which form currently one of the most prominent fields in particle physics. EDM measurements have been concentrated on neutral systems such as the neutron and atoms and molecules. These measurements allow one to deduce, in turn, the electric dipole moments of the fundamental fermions, that is, the lighter leptons and quarks and also those of some heavy nuclei.